Epidemiological characteristics and impact of sepsis on survival after osteoporotic pelvic fracture in Austria - Sokhan, Anton; Haschka, Judith; Reichardt, Berthold; Zwerina, Jochen; Kocijan, Roland; Behanova, Martina (Scientific reports, 2024)
We performed a retrospective nationwide register-based cohort study which included all in-hospital patients aged ≥ 50 with pelvic fracture (PF) between 2010 and 2018 in Austria. We identified patients who were hospitalized with sepsis within 180 days following a PF event. Aetiology of sepsis was divided by unspecified, gram positive, gram negative and other. Among 59,081 patients hospitalized with PF between 2010 and 2018 we identified 619 (1.05%) patients who were hospitalized with sepsis within 180 days following PF. The cumulative incidence risk of sepsis within 180 days after PF was significantly higher in males (1.4%, 95% CI 1.2%-1.5%) as compared to females (0.92%, 95% CI 0.83%-1.0%), p < 0.001. In the cohort of patients with sepsis, the one-year mortality was 50.4%. Mortality risk was greater for patients who developed sepsis, independently of age, sex and comorbidity status (HR 3.12, 95% CI 2.83–3.44, p < 0.001) as compared to patients without sepsis. With a very high one-year mortality risk among those who develop sepsis, our study emphasizes the substantial impact of sepsis on long term survival in fractured patients. These findings underscore the critical need for sepsis prevention and early detection and management to mitigate its detrimental effects on patient outcomes.